2016
DOI: 10.1111/1365-2745.12662
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation, not air temperature, drives functional responses of trees in semi‐arid ecosystems

Abstract: Summary1. Model scenarios of climate change predict that warming and drought will occur simultaneously in the future in many regions. The capacity of woody species to modify their physiology and morphology in response to environmental conditions is widely recognized, but little is known about the responses of trees to reduced precipitation and increased temperature acting simultaneously. 2. In a semi-arid woodland, we assessed the responses in physiological (needle emergence, maximum photosynthesis, stomatal c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
81
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 99 publications
(95 citation statements)
references
References 84 publications
11
81
2
1
Order By: Relevance
“…Low temperatures may have promoted inhibition in chloroplast function, altering the composition of foliar pigments (Maulana & Tesso, ), as well as lower levels of solar irradiance and water availability, especially during vegetative growth (Righi et al, ). Increases in VPD values, as well as low rainfall levels, probably drove the reduction in stomatal conductance, affecting the diffusion of CO 2 into the leaf, leading to decreases in net assimilation rate (Grossiord et al, ). In general, reductions in net assimilation rate during plant growth after full leaf expansion occur, and this decline is generally driven by a decrease in stomatal conductance and transpiration rates (Locke & Ort, ).…”
Section: Discussionmentioning
confidence: 99%
“…Low temperatures may have promoted inhibition in chloroplast function, altering the composition of foliar pigments (Maulana & Tesso, ), as well as lower levels of solar irradiance and water availability, especially during vegetative growth (Righi et al, ). Increases in VPD values, as well as low rainfall levels, probably drove the reduction in stomatal conductance, affecting the diffusion of CO 2 into the leaf, leading to decreases in net assimilation rate (Grossiord et al, ). In general, reductions in net assimilation rate during plant growth after full leaf expansion occur, and this decline is generally driven by a decrease in stomatal conductance and transpiration rates (Locke & Ort, ).…”
Section: Discussionmentioning
confidence: 99%
“…Mean yearly relative extractable water (REW, unitless) calculated using a soil water balance model (Grossiord, Sevanto, Adams, et al, ) and mean yearly air temperature (°C) over the 1997–2016 period at the study site. Starting in 2012 (when treatments started), REW and air temperature are given for each treatment.…”
Section: Methodsmentioning
confidence: 99%
“…Unlike our findings, however, (Garcia-Forner et al, 2016;Grossiord et al, 2017) found no compounding effect of increased drought in addition to increased temperatures. This discrepancy could simply be the result of differing timescales; while a change in climate might not have a measurable response in vegetation in the short term (such as (Bates et al, 2006) observed in the initial years of their study), or be confounded by previous conditions, this climate pattern can have a large enough effect on tree survival to change species distribution in a climate scenario that has been run until steady state.…”
Section: South-facing Slopescontrasting
confidence: 99%
“…Consistently with our results, (Grossiord et al, 2017) demonstrate that Pinus edulis, a tree species common to North America that grows in semi-arid locations, exhibits plastic changes in response to drought, but has only a moderate response to an increase in temperature alone. Unlike our findings, however, (Garcia-Forner et al, 2016;Grossiord et al, 2017) found no compounding effect of increased drought in addition to increased temperatures.…”
Section: South-facing Slopessupporting
confidence: 91%
See 1 more Smart Citation